CORRECTIONAL INFLUENCE OF THE SET ON PROBABILISTIC JUDGMENT - Charkviani, D. (Արդի հոգեբանություն, 2019)
Relevant investigations of psychical mechanisms of probabilistic thinking revealed its bounded rationality reflecting of the specific of subjective comprehension of one other problem by the people. Such cognitive activity of the people plays an important role in the assessment of multiple alternatives and serves to satisfaction their different needs. Considering the main exploratory principles of General Set’s Theory, we assume that functioning of probabilistic judgments determined by relevant set formed in the process of purposive activity of the people. Take into consideration of temporary parameter two forms of the set defined: prospective (orientation on the results of future events) and situational (orientation on results of current events). Obtained experimental data showed: prospective set, compared with situational set, made significant corrective influence on erroneous probabilistic judgments. It indicates the importance of clear cognitive fixation by the subjects of instrumental dependence between primary and secondary expected results.